PERAN KOMUNITAS BEULANGONG TANOH DALAM MELESTARIKAN NILAI-NILAI HISTORICAL UNTUK MENINGKATKAN MEMORI KOLEKTIF MASYARAKAT DI KABUPATEN PIDIE - Fajri, Heri; Zaini, Muhammad; Maulina, Desrika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2023)
Abstract: This article examines the role of the Beulangong Tanoh Community in preserving historical values to improve the collective memory of the people in Pidie District. This research contributes to the study of the continuity of the study of historical values and the collective memory of society in the Pidie context. This research is a qualitative research conducted intensively for three months. The data collection was carried out by interviewing the Beulangong Tanoh Management, namely the Head of Beulangong Tanoh, Secretary, and Head of Publication. In addition, the data in this study were also strengthened by observing techniques for various activities held by the community, as well as collecting data from various documents, both printed and online, related to this research. The results of the study show that the role and contribution of the Beulangong Tanoh Community is by visiting and re-collecting historical and cultural sites in Pidie Regency, turning these data into scientific writings, and uploading these writings on blogs and social media such as Facebook, Instagram and Twitter. In addition, the Beulangong Tanoh Community also held several programs to preserve historical values in improving the community's collective memory, namely publication through blogs and social media, holding discussions related to history and culture, opening historical stands at schools, receiving visits from students and researchers, holding activities meuseuraya (gotong royong), and building cultural networking. Keywords: Role, Beulangong Tanoh Community, Historical Values, Community Collective Memory